Early Exposure to County Income Mobility and Adult Individual Health in the United States. (1st February 2022) - Daza, Sebastian; Palloni, Alberto
Abstract: Objectives: Previous research in the United States suggests contextual income mobility may play a role in explaining the disparities between life expectancy in the United States and peer countries. This article aims to extend previous research by estimating the consequences of average individual exposure to mobility regimes during childhood and adolescence on adult health. Methods: This study draws its data from two longitudinal datasets that track the county of residence of respondents during childhood and adolescence, the Panel Study of Income Dynamics and the National Longitudinal Survey of Youth 1997. We implement marginal structural models to assess the association of the average exposure to county income mobility on five health outcomes and behaviors. Results: The results are only partially consistent with a systematic association between exposure to income mobility and health outcomes. Evidence obtained from the National Longitudinal Survey of Youth suggests less income mobility might increase the probability of smoking by age 30. Discussion: The paper provides a precise assessment of the hypothesis that childhood exposure to income mobility regimes may influence health status through behavior later in life and contribute to longevity gaps. Only partial evidence on smoking suggests an association between income mobility and health, so we discuss potential reasons for the disparities in results with previous research.